Impact of international labor migration on regional economic growth in Thailand - Katikar Tipayalai (Journal of Economic Structures, 2020)
Abstract The movement of labor in the Southeast Asia and particularly Thailand, which is home to more than half of all ASEAN migrant workers, is an issue of growing interest and increasing importance. As Thailand is now confronted with the new challenge of the so-called “middle-income trap”, the Thai government has recently implemented the long-run economic development plan called “Thailand 4.0”, focusing on high productivity and innovative creation from skilled foreign workers. To put Thailand 4.0 in action, the Eastern Economic Corridor (EEC), which is an example of region-based development, serves as a pilot project. However, while demand for high-skilled workers from developed countries increases, the majority of immigrants in Thailand is considered to comprise low-skilled workers from neighboring countries within ASEAN. This article, therefore, examines the impact of international labor migration on regional economic growth in Thailand from 2003 to 2015 through an econometric estimation of the production function by considering the economic consequences of immigration through production and productivity separately for skill-classified migrant workers. The findings empirically indicate that immigrants, and particularly high-skilled ones, have a statistically significant and positive impact on the growth of the regional economy as well as labor productivity in Thailand, thereby suggesting more attention should be paid to the role of regional area-based development policies as well as the ability of the host country to absorb high-skilled migrant workers.